(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This study explores the field of media linguistics, focusing on how language is employed in mass media and the associated challenges in translation. Media linguistics investigates the strategies and stylistic choices used in media language to engage and influence audiences. The research highlights the significance of cultural context and the impact of idiomatic and figurative language on translation processes. Key challenges include the translation of culturally specific references and the need to adapt dynamically evolving language. The study proposes strategies for effective translation, emphasizing contextual adaptation, collaboration with media professionals, and ongoing learning. By addressing these challenges, the research aims to enhance cross-cultural communication and ensure accurate and meaningful media translations.